Two Problem Solving Cycles to Achieve Learning Outcomes of Thinking Skills and Plant Anatomy Concept Mastery (Jurnal Pendidikan IPA Indonesia, 2018)
The purpose of this study was to measure the effectiveness of two problem-solving cycles. The effectiveness of thinking skills was measured through the achievement of learning outcomes of problem solving skills and mastery of the concept of Plant Anatomy. The study was conducted on 96 students at Plant Anatomy course. The research type was quantitative research with a quasi-experiment method. The research design used one group pretest-posttest design. The collected data were analysed descriptively based on the percentage of learning mastery and the average of N-gain. The data indicated a significant difference in the students’ problem-solving skills between the pre-test and post-test with the N-gain value was categorized as a medium level. Moreover, 75% of learning indicators have been completed by the students. In relation to the conceptual understanding, the results showed that the percentages of students who could complete the topics of a stem, a root, and a leaf were 80,21%, 71,88%, and 84,98%, respectively. Therefore, it suggested that the two cycles of problem-solving cycles implemented in this study were effective.